2013
DOI: 10.1186/1476-4598-12-44
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Akt pathway by transcription-independent mechanisms of retinoic acid promotes survival and invasion in lung cancer cells

Abstract: BackgroundAll-trans retinoic acid (ATRA) is currently being used in clinical trials for cancer treatment. The use of ATRA is limited because some cancers, such as lung cancer, show resistance to treatment. However, little is known about the molecular mechanisms that regulate resistance to ATRA treatment. Akt is a kinase that plays a key role in cell survival and cell invasion. Akt is often activated in lung cancer, suggesting its participation in resistance to chemotherapy. In this study, we explored the hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 44 publications
2
30
2
6
Order By: Relevance
“…Previous work has suggested that ILK regulates cell survival through the PI3K/Akt pathway (32), which has also been implicated in cancer cell (33,34) and CSC survival (35,36), cancer cell proliferation (37,38), and the CSC phenotype (39). We found that knockdown of ILK reduced the phosphorylation of Akt (Figure 4A; Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has suggested that ILK regulates cell survival through the PI3K/Akt pathway (32), which has also been implicated in cancer cell (33,34) and CSC survival (35,36), cancer cell proliferation (37,38), and the CSC phenotype (39). We found that knockdown of ILK reduced the phosphorylation of Akt (Figure 4A; Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…ILK is well appreciated for its roles in stemness and metastasis (33,34,37) and is known to stimulate tumor angiogenesis through VEGF-A (51). Our data suggest a positive feedback loop in which the signaling activated by ILK induces increased expression of mechanosensors, including β1-integrin and ILK itself.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that atRA treatment may inhibit the proliferation of glioma cells [19] and mouse embryonic palatal mesenchymal cells [16,17]. atRA-induced proliferation and survival has also been assessed in lung cancer cells [20,21], chicken primordial germ cells and neuronal cells [22]. Investigations of the histopathological effects of retinoic acid on embryonic structure and adult tissues were conducted and revealed that the effect of atRA varies among different tissue organization types [23].…”
Section: Discussionmentioning
confidence: 98%
“…As such, forcing differentiation upon CSCs has attracted considerable attention as a potential anticancer therapy. For example, lung cancer has been shown to be resistant to ATRA treatment, which results in cancer cell promotion [79]. In culture, ATRA readily forces hESCs and hEC cells into a neural differentiation lineage, which is characterized by loss of stemness properties including tumorigenicity.…”
Section: Targeting Cscs Via Forced Differentiationmentioning
confidence: 99%